Prophetic Management of Human Resource Development for Islamic Political Organizations - Zainul Arief; Abdul Hamid; Sarbini Anim (JURNAL ISLAM NUSANTARA, 2025)
This study aims to analyze the application of prophetic management in human resource development (HRD) in Islamic community organizations (ormas) in Indonesia. Prophetic management, which is based on prophetic values such as humanization (amar ma'ruf), liberation (nahi munkar), and transcendence (tu'minuna billah), becomes a relevant ethical and strategic framework in building quality HR with integrity, professionalism, and oriented towards the welfare of the community. This research falls into the library research category, focusing on document and literature studies related to the main research themes. Primary sources include academic journals, scientific books, and research reports that directly examine human resource development for Islamic da'wah, prophetic management, and the internal dynamics of Islamic political parties in Indonesia. The results show that all three have adopted the principles of prophetic management in various forms, such as internalization of spiritual values, strengthening cadre character, a tiered development system, and capacity building through political and Islamic education. However, there are significant variations in its implementation, where PKS tends to be systematic and structured, PPP emphasizes a cultural approach and Islamic boarding school traditions, while PBB focuses on strengthening legalistic and ideological Islamic insights.